The Effectiveness of Administrative Remedies as A Prerequisite For Filing A Lawsuit in Administrative Court - George Muhammad Maulana Helmy Gozali; Hasna Hamidah; Milda Kurnia Herawati; Taufiq Alamsyah (Anthroposia: Journal of Social and Human Development, 2026)
This study examines the effectiveness of administrative remedies as a mandatory prerequisite for filing lawsuits before the Administrative Court within the Indonesian administrative law system. The research employs a non empirical normative juridical approach based on doctrinal legal analysis and extensive library research. Primary legal materials consist of Law Number 5 of 1986 concerning the State Administrative Court, Law Number 30 of 2014 concerning Government Administration, and Supreme Court Regulation Number 6 of 2018. Secondary materials include scholarly literature on administrative justice, governance, accountability, procedural fairness, and the rule of law. The findings indicate that administrative remedies serve an important function in promoting administrative justice by providing opportunities for internal correction, strengthening accountability, and supporting good governance principles. The mechanism also contributes to procedural efficiency by filtering disputes before judicial review. Despite these advantages, its practical effectiveness remains influenced by administrative burdens, regulatory inconsistencies, institutional bias, transparency deficits, and the growing complexity of technology based administrative decision making. The study concludes that administrative remedies possess a strong normative foundation, yet their effectiveness depends substantially on regulatory coherence, institutional capacity, procedural transparency, and adaptive governance capable of responding to contemporary administrative challenges.